Studies of Some Acoustical Properties of 1-(2-Hydroxy-5-Methyl Phenyl)-3-(4'-Methoxy Phenyl)-1,3-Propanedione in 70% Acetone-Water Mixture at 30oC - Agarwal, P.B.; Burghate, A.S.; Idrees Mohd. Siddique, Mohd.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
Ultrasonic velocities and densities of different concentrations of 1-(2-hydroxy-5-methyl phenyl)-3-(4' -methoxy phenyl)-1,3-propanedione in binary mixture (70% acetone-water) have been evaluated at 30oC by using single crystal interferometer at a frequency of 1 MHz. The ultrasonic velocity, density and concentration were used to calculate apparent molal volume (φv), adiabatic compressibility (βs), apparent molal compressibility (φk(s)), intermolecular free length (Lf), specific acoustic impedance (z) and relative association (RA) through the light on the solute-solvent and solute-solute interactions.